Differences in the Quality of Preserved Preservations of Aedes sp Larva in the Clearing Process Using Toluene and Clove Oil - Diah Kinanti Rahayu; Budi Santosa; Toeti Rahajoe; Tulus Ariyadi (Health Notions, 2022)
The purpose of making entomological preserved preparations was to identify insect morphology, which went through the stages of fixation, dehydration, clearing and mounting. Clearing is a step that aims to make the insect structure visible, clear and transparent, the materials used for the clearing process are toluene and clove oil which have carbon compounds and minimal toxicity. The purpose of this study was to determine the quality of preparations preserved by Aedes sp larvae in the clearing process using toluene and clove oil. This type of research was analytic with a cross-sectional approach with two treatments, namely toluene and clove oil, with 16 samples for each treatment. Preserved preparations of Aedes sp. larvae were observed microscopically to assess the quality of preserved preparations which included the clarity of preparations, color quality, and the integrity of the parasite's limbs. The results showed that in the clearing treatment with toluene, 5 preparations were of good quality, 4 preparations of good quality, and 7 preparations of poor quality. Clearing treatment with clove oil obtained 12 preparations of good quality and 4 preparations of moderate quality. The Mann-Whitney statistical test showed a p-value of 0.032. It can be concluded that there is difference in the quality of preparations preserved by Aedes sp. larvae in the clearing process using toluene and clove oil. Keywords: quality of preparations; Aedes sp; toluene; clove oil